Methods Used in Teaching Psychology - Сейтбаева Гульхумар Бахадыр-кызы (European Science Publishing, 2023)
The pedagogical process is organized directly by the teacher. Wherever and by what kind of teacher the pedagogical process is organized, it will have the same structure: goal-principles-content-methods-means. The goal reflects the final results of joint pedagogical actions, to which the teacher and the student aspire. The principles are designed to determine the main directions for achieving the goal. Content is part of the ancestral experience that is given to students to achieve goals in of the selected area.
Keywords: Psychology, pedagogy, methodology, method, pedagogical process, education, science.